Versatile MXene integrated assembly for piezoresistive micro‐force sensing. Issue 5 (16th November 2022) - Wang, Shenglong; Lan, Boling; Gao, Yuyu; Xie, Yanting; He, Hanyu; Xiong, Da; Tian, Guo; Yang, Tao; Huang, Junfeng; Ao, Yong; Sun, Yue; Yang, Weiqing; et al.
Abstract: MXenes have received tremendous attention for flexible electronics owing to their excellent conductivity, water dispersibility, and mechanical flexibility. However, the sediment from the MXene production process is usually discarded as trash, resulting in low utilization. Here, we present a flexible pressure sensor that enables micro‐force sensing and efficient utilization of MXene by confining MXene trash among structured MXene electrodes. Benefiting from the synergistic effect of both the confined micro‐conical structure and easily changeable space of MXene trash, the as‐designed device can detect extremely subtle pressure of 2.9 Pa, deliver a high sensitivity over 4.08 kPa −1, and exhibit a remarkably fast response time (7 ms). These properties make it suitable for monitoring weak force signals from human wrist pulse and even for detecting dynamic responses associated with acoustic waves. This work provides a reference for the versatile and efficient application of MXene in the same device, showing great potential for sustainable production of next‐generation wearable smart electronics. Abstract : MXenes have received tremendous attention for flexible electronics. We present a flexible pressure sensor that enables micro‐force sensing and efficient utilization of MXene by confining MXene trash between structured MXene electrodes. The as‐designed device can detect subtle pressure of 2.9 Pa, and exhibit a fast response time (7 ms). And it can be used for human physiological signal monitoring and sound recording, showing great potential for wearable electronics.